Concepts for Model Verification and Validation during Simulation Runtime - Laroque, Christoph; Fischer, Matthias; Dangelmaier, Wilhelm (European Simulation and Modelling Conference (ESM 2009))
Modern companies are nowadays confronted with an increasing demand of multiple products, where they need to perform more flexible every day. Cost-intensive decisions are to be confirmed in short times, in order to minimize risks and secure efficient production programs as well as material flows. Tools for this digital planning via simulation methods are one well established possibility to receive decision support. Nevertheless, the creation of the necessary simulation models is a complicated and error-prone process, where complexity of modeling, validation and verification depends on the used tool and its functionalities. This paper presents implemented concepts for an innovative user support in his tasks of verification and validation of simulation models during the execution of a simulation run. Time-intensive procedures like stopping simulation, parameterization and restarting within the problem analysis are simplified. So the user is able to focus on the real problem solving task.

Improving Network Coded Cooperation by Soft Information - Volkhausen, Tobias; Woldegebreal, Dereje H.; Karl, Holger (2009 6th IEEE Annual Communications Society Conference on Sensor, Mesh and Ad Hoc Communications and Networks Workshops)

Combining for Cooperative WLANs - A Reality Check Based on Prototype Measurements - Valentin, S.; Woldegebreal, D. H.; Volkhausen, T.; Karl, Holger (2009 IEEE International Conference on Communications Workshops)

Ein System zur aggregierten Visualisierung verteilter Materialflusssimulationen - Suess, Tim; Fischer, Matthias; Huber, Daniel; Laroque, Christoph; Dangelmaier, Wilhelm (Augmented & Virtual Reality in der Produktentstehung)

Creating Butterflies in the Core – A Network Coding Extension for MPLS/RSVP-TE - Biermann, Thorsten; Schwabe, Arne; Karl, Holger (NETWORKING 2009)

Modeling obstacles in INET/Mobility framework: motivation, integration, and performance - Lichte, Hermann S.; Weide, Jannis (Proceedings of the Second International ICST Conference on Simulation Tools and Techniques)

Design considerations for a network of information - Ahlgren, Bengt; Vercellone, Vinicio; D'Ambrosio, Matteo; Marchisio, Marco; Marsh, Ian; Dannewitz, Christian; Ohlman, Börje; Pentikousis, Kostas; Strandberg, Ove; Rembarz, René (Proceedings of the 2008 ACM CoNEXT Conference on - CONEXT '08)

Planar Visibility Counting - Fischer, Matthias; Hilbig, Matthias; Jähn, Claudius; Meyer auf der Heide, Friedhelm; Ziegler, Martin (Proc. 25th European Workshop on Computational Geometry)
For a fixed virtual scene (=collection of simplices) S and given observer position p, how many elements of S are weakly visible (i.e. not fully occluded by others) from p? The present work explores the trade-off between query time and preprocessing space for these quantities in 2D: exactly, in the approximate deterministic, and in the probabilistic sense. We deduce the EXISTENCE of an O(m^2/n^2) space data structure for S that, given p and time O(log n), allows to approximate the ratio of occluded segments up to arbitrary constant absolute error; here m denotes the size of the Visibility Graph--which may be quadratic, but typically is just linear in the size n of the scene S. On the other hand, we present a data structure CONSTRUCTIBLE in O(n*log(n)+m^2*polylog(n)/k) preprocessing time and space with similar approximation properties and query time O(k*polylog n), where k<n is an arbitrary parameter. We describe an implementation of this approach and demonstrate the practical benefit of the parameter k to trade memory for query time in an empirical evaluation on three classes of benchmark scenes.

Measurement of effective electron mass in biaxial tensile strained silicon on insulator - Feste, Sebastian F.; Schäpers, Thomas; Buca, Dan; Zhao, Qing Tai; Knoch, Joachim; Bouhassoune, Mohammed; Schindlmayr, Arno; Mantl, Siegfried (Applied Physics Letters)
We present measurements of the effective electron mass in biaxial tensile strained silicon on insulator (SSOI) material with 1.2 GPa stress and in unstrained SOI. Hall-bar metal oxide semiconductor field effect transistors on 60 nm SSOI and SOI were fabricated and Shubnikov–de Haas oscillations in the temperature range of T=0.4–4 K for magnetic fields of B=0–10 T were measured. The effective electron mass in SSOI and SOI samples was determined as mt=(0.20±0.01)m0. This result is in excellent agreement with first-principles calculations of the effective electron mass in the presence of strain.

Überlegung zur Senkung des Energieeintrags bei der Compoundierung - Hallmann, Tobias; Schöppner, Volker; Fiekens, Nicolas; Zimmer, Detmar (VDI-Fachtagung Aufbereitungstechnik)

Methodische Modularisierung komplexer Produktstrukturen - Fiekens, Nicolas; Zimmer, Detmar (Konferenz Variantenmanagement im Produktentstehungsprozess im Maschinen- und Anlagenbau)

An Orchestration as a Service Infrastructure using Grid Technologies and WS-BPEL - Höing, Andre; Scherp, Guido; Gudenkauf, Stefan; Meister, Dirk; Brinkmann, André (Proc. Int. Conf. on Service Oriented Computing (ICSOC))

Providing Scientific Software as a Service in Consideration of Service Level Agreements - Niehörster, Oliver; Birkenheuer, Georg; Brinkmann, André; Blunk, Dirk; Elsässer, Brigitta; Herres-Pawlis, Sonja; Krüger, Jens; Niehörster, Julia; Packschies, Lars; Fels, Gregor (Proc. Cracow Grid Workshop (CGW))

Connecting Communities on the Meta-Scheduling Level: The DGSI Approach! - Birkenheuer, Georg; Carlson, Arthur; Fölling, Alexander; Högqvist, Mikael; Hoheisel, Andreas; Papaspyrou, Alexander; Rieger, Klaus; Schott, Bernhard; Ziegler, Wolfgang (Proc. Cracow Grid Workshop (CGW))

Multi-Level Comparison of Data Deduplication in a Backup Scenario - Meister, Dirk; Brinkmann, André (Proc. of the Israeli Experimental Systems Conference (SYSTOR))

Solution Patterns for the Development of Self-Optimizing Systems - Dumitrescu, Roman; Gausemeier, Jürgen; Dangelmaier, Wilhelm; Klöpper, Benjamin (Self-x in Engineering)

Control of the Pareto Optimality of Systems with Unknown Disturbances - Geisler, Jens; Trächtler, Ansgar (7th IEEE International Conference on Control & Automation (ICCA 2009))

Parametrische Modellreduktion für selbstoptimierende mechatronische Systeme - Krüger, Martin (Tagungsband Workshop GMA-Fachausschuß 1.30/1.40)

Control Strategy for the Lateral and Longitudinal Dynamics of a Fully Active X-by-wire Test Vehicle - Reinold, Peter; Nachtigal, Vitalij; Jäker, Karl-Peter; Trächtler, Ansgar (Proceedings of the European Control Conference 2009 (ECC))

Prototypische Applikation einer Vereinzelungsregelung an einem Bankautomaten - Just, Viktor; Cinkaya, Hueseyin; Trächtler, Ansgar; Jäker, Karl-Peter (Mechatronik 2009 VDI)

Entwicklung einer Hardware-in-the-Loop-Umgebung für den Steuergerätetest von Kondenstrocknern - Zeineldin, Tarek; Koert, Dirk; Löffler, Alexander; Trächtler, Ansgar (VDI Mechatronik)

RailCab Ein innovatives Schienenverkehrssystem für die Mobilität von morgen - Rustemeier, Carsten; Trächtler, Ansgar (Ingenieurspiegel Fachmagazin für Ingenieure)

Entwurf einer adaptiven Regelung für den Vereinzelungsvorgang in Bankautomaten - Just, Viktor; Cinkaya, Hueseyin; Trächtler, Ansgar; Jäker, Karl-Peter (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Aufbau und Regelung eines sturzvariablen Bahnfahrwerks mit Einzelradlenkung - Borsig, Michael; Trächtler, Ansgar; Geisler, Jens (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Echtzeitsimulation für den modellbasierten Steuergerätetest von Haushaltsgeräten - Koert, Dirk; Löffler, Alexander; Zeineldin, Tarek; Trächtler, Ansgar (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Entwurf einer semiaktiven Federung für ein leichtes Kettenfahrzeug - Illg, Igor; Jäker, Karl-Peter; Trächtler, Ansgar (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Flachheitsbasierte Reglerumschaltstrategie für Ein- und Mehrgrößensysteme - Osmic, Semir (43. Regelungstechnisches Kolloquium)

Kreuzungsmanagement: Trajektorienplanung mittels dynamischer Programmierung - Bruns, Torsten; Trächtler, Ansgar (at-Automatisierungstechnik)

Verlässlichkeit im aktiven selbstoptimierenden Spurführungsmodul eines schienengebundenen Fahrzeugs - Sondermann-Wölke, Christoph; Geisler, Jens; Hirsch, Martin; Hemsel, Tobias (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Selbstoptimierende Systeme des Maschinenbaus Definitionen, Anwendungen, Konzepte - Adelt, Philipp; Donoth, Jörg; Gausemeier, Jürgen; Geisler, Jens; Henkler, Stefan; Kahl, Sascha; Klöpper, Benjamin; Krupp, Alexander; Münch, Eckehard; Oberthür, Simon; Paiz, Carlos; Porrmann, Mario; et al. (HNI-Verlagsschriftenreihe)

Verlässlichkeit selbstoptimierender Systeme. Potenziale nutzen und Risiken vermeiden - Dell'Aere, Alessandro; Hirsch, Martin; Klöpper, Benjamin; Koester, Markus; Krupp, Alexander; Krüger, Martin; Müller, Thomas; Oberthür, Simon; Pook, Sebastian; Priesterjahn, Claudia; Romaus, Christoph; Schmidt, Alexander; et al.

Fahrdynamische Regelungen und Fahrzeugführung - Trächtler, Ansgar (at-Automatisierungstechnik)

Probabilistic Planning Integrated in a Multi-level Dependability Concept for Mechatronic Systems - Klöpper, Benjamin; Sondermann-Wölke, Christoph; Romaus, Christoph; Voecking, Henner (IEEE-CICA 2009)

Control of the Pareto Optimality of Systems with Unknown Disturbances - Geisler, Jens; Trächtler, Ansgar (7th IEEE International Conference on Control & Automation (ICCA 2009))

Parametrische Modellreduktion für selbstoptimierende mechatronische Systeme - Krüger, Martin (Tagungsband Workshop GMA-Fachausschuß 1.30/1.40)

Control Strategy for the Lateral and Longitudinal Dynamics of a Fully Active X-by-wire Test Vehicle - Reinold, Peter; Nachtigal, Vitalij; Jäker, Karl-Peter; Trächtler, Ansgar (Proceedings of the European Control Conference 2009 (ECC))

Prototypische Applikation einer Vereinzelungsregelung an einem Bankautomaten - Just, Viktor; Cinkaya, Hueseyin; Trächtler, Ansgar; Jäker, Karl-Peter (Mechatronik 2009 VDI)

Entwicklung einer Hardware-in-the-Loop-Umgebung für den Steuergerätetest von Kondenstrocknern - Zeineldin, Tarek; Koert, Dirk; Löffler, Alexander; Trächtler, Ansgar (VDI Mechatronik)

RailCab Ein innovatives Schienenverkehrssystem für die Mobilität von morgen - Rustemeier, Carsten; Trächtler, Ansgar (Ingenieurspiegel Fachmagazin für Ingenieure)

Entwurf einer adaptiven Regelung für den Vereinzelungsvorgang in Bankautomaten - Just, Viktor; Cinkaya, Hueseyin; Trächtler, Ansgar; Jäker, Karl-Peter (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Aufbau und Regelung eines sturzvariablen Bahnfahrwerks mit Einzelradlenkung - Borsig, Michael; Trächtler, Ansgar; Geisler, Jens (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Echtzeitsimulation für den modellbasierten Steuergerätetest von Haushaltsgeräten - Koert, Dirk; Löffler, Alexander; Zeineldin, Tarek; Trächtler, Ansgar (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Entwurf einer semiaktiven Federung für ein leichtes Kettenfahrzeug - Illg, Igor; Jäker, Karl-Peter; Trächtler, Ansgar (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Flachheitsbasierte Reglerumschaltstrategie für Ein- und Mehrgrößensysteme - Osmic, Semir (43. Regelungstechnisches Kolloquium)

Kreuzungsmanagement: Trajektorienplanung mittels dynamischer Programmierung - Bruns, Torsten; Trächtler, Ansgar (at-Automatisierungstechnik)

Verlässlichkeit im aktiven selbstoptimierenden Spurführungsmodul eines schienengebundenen Fahrzeugs - Sondermann-Wölke, Christoph; Geisler, Jens; Hirsch, Martin; Hemsel, Tobias (6. Paderborner Workshop: "Entwurf mechatronischer Systeme")

Selbstoptimierende Systeme des Maschinenbaus Definitionen, Anwendungen, Konzepte - Adelt, Philipp; Donoth, Jörg; Gausemeier, Jürgen; Geisler, Jens; Henkler, Stefan; Kahl, Sascha; Klöpper, Benjamin; Krupp, Alexander; Münch, Eckehard; Oberthür, Simon; Paiz, Carlos; Porrmann, Mario; et al. (HNI-Verlagsschriftenreihe)

Verlässlichkeit selbstoptimierender Systeme. Potenziale nutzen und Risiken vermeiden - Dell'Aere, Alessandro; Hirsch, Martin; Klöpper, Benjamin; Koester, Markus; Krupp, Alexander; Krüger, Martin; Müller, Thomas; Oberthür, Simon; Pook, Sebastian; Priesterjahn, Claudia; Romaus, Christoph; Schmidt, Alexander; et al.

Fahrdynamische Regelungen und Fahrzeugführung - Trächtler, Ansgar (at-Automatisierungstechnik)

Probabilistic Planning Integrated in a Multi-level Dependability Concept for Mechatronic Systems - Klöpper, Benjamin; Sondermann-Wölke, Christoph; Romaus, Christoph; Voecking, Henner (IEEE-CICA 2009)

Education Programme at Eurographics 2009 - Domik, Gitta; Scateni, Riccardo (Computer Graphics Forum)

Quantitative myocardial perfusion PET combined with coronary anatomy derived from CT angiography: Validation of a new fusion and visualisation software - Fricke, Harald; Elsner, Andreas; Weise, Reiner; Bolte, Matthias; van den Hoff, Jörg; Burchert, Wolfgang; Domik, Gitta; Fricke, Eva (Zeitschrift für Medizinische Physik)
Keywords: Coronary artery disease; CT angiography; cardiac PET; quantitative perfusion measurement; Koronare Herzerkrankung; CT-Angiographie; PET; quantitative Perfusionsmessung

Proceedings of the Workshop on Model Driven Development of Advanced User Interfaces (MDDAUI'09), Sanibel Island (FL, USA)

Proceedings of Design for Future - 1. Workshop des GI-Arbeitskreises "Langlebige Softwaresysteme (L2S2)"

Who Owns the Customer? Disentangling Customer Loyalty in Indirect Distribution Channels - Eggert, A; Henseler, J; Hollmann, S (Proceedings of the 17th International Colloquium in Relationship Marketing)

Can Successful Customer Acquisition Hurt the Existing Customer Base? - Woisetschläger, D; Garnefeld, I; Eggert, A (Proceedings of the 2009 AMA Summer Marketing Educators' Conference)

Referral reward programs: New customer acquisition by opportunism? - Garnefeld, I; Münkhoff, E; Hogreve, J; Eggert, A (Proceedings of the 15th Academy of Marketing Science (AMS) World Marketing Congress)

Musing on a Decade of Customer Value Research in Business Relationships: Where Do We Come From? Where Should We Go? - Eggert, A; Ulaga, W (Proceedings of the 4th International Conference on Business Market Management)

Customer Referral Programs and Customer Retention – Do Rewards Undermine the Retention Effect? - Garnefeld, I; Helm, S; Tax, S; Eggert, A (Proceedings of the 2009 AMA Winter Educators' Proceedings)

Unintended effects of referral reward programs: Exploring the impact of rewards on opportunistic behavior - Garnefeld, I; Münkhoff, E; Hogreve, J; Eggert, A (Proceedings of the 38th European Marketing Academy (EMAC) Conference)

Who Owns the Customer? Exploring Customer Loyalty in a Channel Context - Eggert, A; Henseler, J; Hollmann, S (Proceedings of the 38th European Marketing Academy (EMAC) Conference)

Nonlocal Aharonov–Bohm conductance oscillations in an asymmetric quantum ring - Buchholz, S. S.; Fischer, S. F.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Language-Independent Change Management of Process Models - Gerth, Christian; Küster, Jochen; Engels, Gregor (Proceedings of the ACM/IEEE 12th International Conference on Model Driven Engineering Languages and Systems (MODELS'09). Denver (CO, USA))
In model-driven development approaches, process models are used at different levels of abstraction and are described by different languages. Similar to other software artifacts, process models are developed in team environments and underlie constant change. This requires reusable techniques for the detection of changes between different process models and the computation of dependencies and conflicts between changes. In this paper, we propose a framework for the construction of process model change management solutions that provides generic techniques for the detection of differences and the computation of dependencies and conflicts between changes. The framework contains an abstract representation for process models that serves as a common denominator for different process models. In addition, we show how the framework is instantiated exemplarily for BPMN.

SOA-Business Case - Assmann, Martin; Haack, Markus; Scheider, Hendrik; vom Hagen, Nico; Zacharias, Roger (Transform IT: Optimale Geschäftsprozesse durch eine transformierende IT)

A Holistic Software Engineering Method for Service-Oriented Application Landscape Development - Baumann, Andrea; Engels, Gregor; Hofmann, Alexander; Sauer, Stefan; Willkomm, Johannes (Proceedings of the First NAF Academy Working Conference on Practice-Driven Research on Enterprise Transformation (PRET 2009), Amsterdam (The Netherlands))
Enterprises are transforming into enterprises which follow from a business as well as from an IT perspective a service-oriented paradigm. This change towards service-oriented enterprise and IT architectures has to be reflected in the methodologies of developing whole application landscapes as well as individual applications. Quasar (Quality Software Architecture) has been developed as the standard architecture and development method of Capgemini sd&m for individual applications. For the development of service-oriented enterprise application landscapes, Quasar Enterprise has been designed. Both Quasar and Quasar Enterprise are integrated with each other within a holistic software engineering method to seamlessly cover the full development lifecycle of service-oriented application landscapes, from business modeling and service design to actual software development. In this paper, we illustrate how a company-wide ontology of development artifacts serves as the key feature for integrating both methods.

Model Driven Development of Advanced User Interfaces 2009 - Meixner, Gerrit; Görlich, Daniel; Breiner, Kai; Hußmann, Heinrich; Pleuß, Andreas; Sauer, Stefan; Van den Bergh, Jan (Proceedings of the 2009 International Conference on Intelligent User Interfaces)

Dependent and Conflicting Change Operations of Process Models - Küster, Jochen; Gerth, Christian; Engels, Gregor (Proceedings of the 5th European Conference on Model-Driven Architecture Foundations and Applications (ECMDA-FA'09))
Version management of models is common for structural diagrams such as class diagrams but still challenging for behavioral models such as process models. For process models, conflicts of change operations are difficult to resolve because often dependencies to other change operations exist. As a consequence, conflicts and dependencies between change operations must be computed and shown to the user who can then take them into account while creating a consolidated version. In this paper, we introduce the concepts of dependencies and conflicts of change operations for process models and provide a method how to compute them. We then discuss different possibilities for resolving conflicts. Using our approach it is possible to enable version management of process models with minimal manual intervention of the user.

Sicherstellen der Betrachtung von nicht-funktionalen Anforderungen in SCRUM-Prozessen durch Etablierung von Feedback - Engels, Gregor; Geisen, Silke; Sauer, Stefan; Port, Olaf (Informatik 2009 - Im Focus das Leben)

Integrated Specification and Quality Assurance for Large Business Information Systems - Salger, Frank; Sauer, Stefan; Engels, Gregor (Proceedings of the 2nd India Software Engineering Conference (ISEC'09))

Model-Based System Testing Using Visual Contracts - Güldali, Baris; Mlynarski, Michael; Wübbeke, Andreas; Engels, Gregor (Proceedings of Euromicro SEAA Conference 2009, Special Session on “Model Driven Engineering”)

Zautomatyzowane testy akceptacyjne dla aplikacji internetowych w programowaniu sterowanym testami - Mlynarski, Michael; Jureczko, Marian (Proceedings of Krajowa Konferencja In?ynierii Oprogramowania 2009)

A UML Framework for IP-XACT-based IP Management - Schattkowsky, Tim; Xie, Tao (Proceedings of the conference on Design Automation and Test in Europe (DATE 2009), Nice (France))

Towards Test-Driven Semantics Specification - Soltenborn, Christian; Engels, Gregor (Proceedings of the 12th International Conference on Model Driven Engineering Languages and Systems (MODELS 2009), Denver, Colorado (USA))
Behavioral models are getting more and more important within the software development cycle. To get the most use out of them, their behavior should be defined formally. As a result, many approaches exist which aim at specifying formal semantics for behavioral languages (e.g., Dynamic Meta Modeling (DMM), Semantic Anchoring). Most of these approaches give rise to a formal semantics which can e.g. be used to check the quality of a particular language instance, for instance using model checking techniques. However, if the semantics specification itself contains errors, it is more or less useless, since one cannot rely on the analysis results. Therefore, the language engineer must make sure that the semantics he develops is of the highest quality possible. To help the language engineer to achieve that goal, we propose a test-driven semantics specification process: the semantics of the language under consideration is first informally demonstrated using example models, which will then be used as test cases during the actual semantics specification process. In this paper, we present this approach using the already mentioned specification language DMM.

Improving Reusability of Dynamic Meta Modeling Specifications with Rule Overriding - Engels, Gregor; Fisseler, Daniela; Soltenborn, Christian (Proceedings of the 2009 IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC 2009), Corvallis, Oregon (USA))

Semi-automated Test Planning for e-ID Systems by Using Requirements Clustering - Güldali, Baris; Funke, Holger; Jahnich, Michael; Sauer, Stefan; Engels, Gregor (24th IEEE/ACM International Conference on Automated Software Engineering (ASE 2009), 16-20 November 2009, Auckland, New Zeland)
In acceptance testing, customer requirements as specified in system specifications have to be tested for their successful implementation. This is a time-consuming task due to inherent system complexity and thus a large number of requirements. In order to reduce efforts in acceptance testing, we introduce a novel approach that exploits redundancies and implicit relations in requirements specifications, which are based on multi-viewpoint techniques, in our case the reference model for open distributed processing (RM-ODP). It deploys requirements clustering and linguistic analysis techniques for reducing the total number of test cases. We report on concrete experiences with this approach within joint R&D work of the Software Quality Lab (s-lab) of the University of Paderborn and HJP Consulting, an international consulting company, specialized in planning, procurement and acceptance testing of national electronic identification (e-ID) systems. The paper is concluded with an overview on the current tool support especially for automated detection of the redundancies and implicit relations in requirements. Also the future work on the tool support for the overall test specification process is discussed.

Identifying Software Product Line Component Services - Assmann, Martin; Engels, Gregor; von der Maßen, Thomas; Wübbeke, Andreas (Proceedings of International Conference on Evaluation of Novel Approaches to Software Engineering (ENASE 09))

Flow Synchronization for Network Coding - Biermann, Thorsten; Dräxler, Martin; Karl, Holger (Journal of Communications)

Cooperative Wireless Networking Beyond Store-and-Forward - Valentin, Stefan; S. Lichte, Hermann; Karl, Holger; Vivier, Guillaume; Simoens, Sebastien; Vidal, Josep; Agustin, Adrian (Wireless Personal Communications)

An Adaptive Resource/Performance Trade-Off for Resolving Complex Queries in P2P Networks - Biermann, Thorsten; Dannewitz, Christian; Karl, Holger (Proceedings of IEEE International Conference on Communications, ICC 2009, Dresden, Germany, 14-18 June 2009)

Rate-Per-Link Adaptation in Cooperative Wireless Networks with Multi-Rate Combining - S. Lichte, Hermann; Valentin, Stefan; von Malm, Holger; Karl, Holger; Bin Sediq, Akram; Aad, Imad (Proceedings of IEEE International Conference on Communications, ICC 2009, Dresden, Germany, 14-18 June 2009)

The Gain of Overbooking - Birkenheuer, Georg; Brinkmann, Andre; Karl, Holger (Job Scheduling Strategies for Parallel Processing, 14th International Workshop, JSSPP 2009, Rome, Italy, May 29, 2009. Revised Papers)

Analyzing space/capacity tradeoffs of cooperative wireless networks using a probabilistic model of interference - Simon Lichte, Hermann; Valentin, Stefan; Karl, Holger; Aad, Imad; Widmer, J. (Proceedings of the 12th International Symposium on Modeling Analysis and Simulation of Wireless and Mobile Systems, MSWiM 2009, Tenerife, Canary Islands, Spain, October 26-19, 2009)

Creating Butterflies in the Core - A Network Coding Extension for MPLS/RSVP-TE - Biermann, Thorsten; Schwabe, Arne; Karl, Holger (NETWORKING 2009, 8th International IFIP-TC 6 Networking Conference, Aachen, Germany, May 11-15, 2009. Proceedings)

A virtual network mapping algorithm based on subgraph isomorphism detection - Lischka, Jens; Karl, Holger (Proceedings of the 1st ACM SIGCOMM Workshop on Virtualized Infrastructure Systems and Architectures, VISA 2009, Barcelona, Spain, August 17, 2009)

“Metriken” – Kennzahlen zur Verbesserung der Softwarequalität, Teile 1 und 2 - Gehrke, Matthias; Güldali, Baris; Meyer, Jan; Sancar, Yavuz; Spijkerman, Michael

"Metriken" - Kennzahlen zur Verbesserung der Softwarequalität, Teile 1 und 2 - Gehrke, Matthias; Güldali, Baris; Meyer, Jan; Sancar, Yavuz; Spijkerman, Michael

PV module characterization - Krauter, Stefan; Grunow, Paul (Photovoltaics International)

Book of Proceedings of RIO 9 – World Climate & Energy Event

Acceptance of Remote Services – Perception, Adoption, and Continued Usage in Organizational Settings - Wünderlich, Nancy
The increasing employment of information and communication technologies in companies and households has led to considerable changes in the way services are conceived, developed, and delivered. Nancy V. Wünderlich employs a multi-method approach comprising an international qualitative study in Germany, USA and China and a longitudinal quantitative study to analyze remote services. She develops the Interactive Technology-Mediated Service Model (ITSUM) to provide a comprehensive approach of explaining both initial acceptance and repeated, continued usage of remote services in organizations. Finally, she derives managerial implications for remote service providers on how to increase remote service acceptance among their customers and facilitate the export of remote services.

Evaluierung von Bewertungsmodellen für den Testprozess - Yigitbas, Enes

Vorteil Interim Management - Kabst, Rüdiger; Thost, W; Isidor, R

Was zeichnet den erfolgreichen Interim Manager aus? - Kabst, Rüdiger; Isidor, R; Thost, W; Linné, H

Manager auf Zeit: Ignoriert oder akzeptiert? - Kabst, Rüdiger; Isidor, R; Thost, W; Nagel, R

International Fachkräfte gewinnen - Kabst, Rüdiger; Salow, S; Baum, M

Editorial: Motivieren trotz Krise - Kabst, Rüdiger

Editorial: Zukunft sichern - Kabst, Rüdiger

International komparatives Personalmanagement: Evidenz, Methodik & Klassiker des "Cranfield Projects on International Human Resource Management" - Kabst, Rüdiger; Giardini, A; Wehner, M C

Ausgewählte Stichwörter zum internationalen Personalmanagement - Kabst, Rüdiger; Giardini, A (Vahlens großes Personal Lexikon)

Das Cranfield Project on International Strategic Human Resource Management: Eine Einführung - Kabst, Rüdiger; Giardini, A; Wehner, M C (International komparatives Personalmanagement: Evidenz, Methodik & Klassiker des “Cranfield Projects on International Human Resource Management”)

Das Lernverhalten früh internationalisierender Unternehmen: ein konzeptioneller Analyserahmen. - Schwens, C; Kabst, Rüdiger (Internationale Unternehmensführung - Entscheidungsfelder und politische Aspekte.)